Alasan-Alasan Pengusiran pada Legenda Sangkuriang dalam Perspektif Sastra Bandingan: Reasons for expulsion in the Sangkuriang legend in a comparative literature perspective - Mukodas, Mukodas; Miranti, Miranti; Nurjaman, Aam (Journal of Literature and Education, 2024)
The legend of Sangkuriang is often associated with the creation of Mount Tangkuban Perahu in West Java. It has been retold in various versions, including children's folklore and deconstructed narratives. Regardless of the variation, the story always involves instances of expulsion. There are three expulsions: the expulsion of the god into a dog and the goddess into a pig; the expulsion of Dayang Sumbi into the wilderness; and the expulsion of Sangkuriang by Dayang Sumbi. This study aims to compare the similarities and differences in the reasons behind these expulsions. By understanding the reasons behind the characters' expulsions, readers are encouraged to avoid making the same mistakes in the real world. The research utilizes a qualitative descriptive method with a comparative literary analysis technique, comparing two works: the Indonesian retelling of Cerita Rakyat Sangkuriang by Harnaeni Hamdan and the deconstructed novel Sangkuriang Garing by Givi Givani in the Sundanese language. The result of this research is that the expulsion happened because of forbidden love, pregnancy outside marriage, and killing one's father.